2021
DOI: 10.1200/jco.20.01359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Patient-Matched Molecular Composition of Relapsed Medulloblastoma

Abstract: PURPOSE We sought to investigate clinical outcomes of relapsed medulloblastoma and to compare molecular features between patient-matched diagnostic and relapsed tumors. METHODS Children and infants enrolled on either SJMB03 (NCT00085202) or SJYC07 (NCT00602667) trials who experienced medulloblastoma relapse were analyzed for clinical outcomes, including anatomic and temporal patterns of relapse and postrelapse survival. A largely independent, paired molecular cohort was analyzed by DNA methylation array and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
61
3
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 29 publications
14
61
3
22
Order By: Relevance
“…Downloaded from https://academic.oup.com/neuro-oncology/advance-article/doi/10.1093/neuonc/noab178/6323243 by University of Northumbria user on 04 October 2021 characteristics. This is in contrast to findings by Kumar et al, which similarly reported subtype divergence in 15/69 rMB (subtypes III, V, VI, VII, VIII at diagnosis), and proffered an association with MYC amplification or chromosome 2p gain at relapse 11. However, such cases were infrequent in both studies, and the nature, biological and clinical significance of these rare subtype switchers requires further investigation.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…Downloaded from https://academic.oup.com/neuro-oncology/advance-article/doi/10.1093/neuonc/noab178/6323243 by University of Northumbria user on 04 October 2021 characteristics. This is in contrast to findings by Kumar et al, which similarly reported subtype divergence in 15/69 rMB (subtypes III, V, VI, VII, VIII at diagnosis), and proffered an association with MYC amplification or chromosome 2p gain at relapse 11. However, such cases were infrequent in both studies, and the nature, biological and clinical significance of these rare subtype switchers requires further investigation.…”
contrasting
confidence: 92%
“…[7][8][9][10] Most recently, Kumar et al showed that the degree and patterns of molecular conservation at relapse vary according to disease subgroup. 11 Mutations of TP53 have been commonly identified in rMB, and can be both selectively maintained from diagnosis,…”
mentioning
confidence: 99%
“…To increase the applicability of this therapeutic paradigm, we may take into consideration the fact that patients with recurrent MB often present with LC/A histology and with TP53 mutations that were undetected in the primary tumor ( 46 ). In fact, loss of function of Trp53 is identified as a key event in the pathogenesis of recurrence ( 38 , 46 48 ). Specifically, genetic events in TP53 pathway genes or in the actual TP53 gene are frequent in recurrences, predominantly in SHH MB ( 38 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, loss of function of Trp53 is identified as a key event in the pathogenesis of recurrence ( 38 , 46 48 ). Specifically, genetic events in TP53 pathway genes or in the actual TP53 gene are frequent in recurrences, predominantly in SHH MB ( 38 , 48 ). Very interestingly, the mouse model used for modeling posttreatment MB recurrence, namely a Tp53 mut transposon-driven MB model, shows large cells, nuclear atypia, and nuclear molding that are all typical features of LC/A histology ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MYCN has received less attention with respect to pediatric brain tumors, while recent reports have highlighted its role in the disease [ 9 , 10 , 11 ]. Apart from its role in neuroblastoma, MYCN has been studied in some extent for other pediatric brain neoplasms such as medulloblastoma [ 12 , 13 ], astrocytoma [ 14 ], glioblastoma [ 15 , 16 ], and others. One of the main questions in MYCN biology is the link between its overexpression and amplification.…”
Section: Introductionmentioning
confidence: 99%